Crime survey for England and Wales, 2013-2014: unrestricted access teaching dataset (UK Data Service, 2019)
This Unrestricted Access Teaching Dataset is based on the Crime Survey for England and Wales (CSEW), 2013-2014. It has been prepared for teaching and student use only with the aim of helping class tutors incorporate empirical data into their courses and supporting students to develop skills in quantitative data analysis. It contains data for 8,843 cases from the CSEW 2013-14 (non-victim form dataset) for a small selection of variables. Most variables come directly from the CSEW 2013-14. However, some variables have been recoded and additional scalar variables have been added to support teaching and learning.